Computerization of land titles: a case study in Shah Alam / Nur Alia Mohamed Noor Rosli and Nurrul Nadia Norrizan - Mohamed Noor Rosli, Nur Alia; Norrizan, Nurrul Nadia (2007)
In 2004, a case was reported in the local newspaper regarding an illegal transfer of land ownership in Shah Alam. This illegal transfer was done not by an outsider, but by an employee at the Selangor Land Office. This case raised doubts on the effectiveness of the Computerized Land Registration System adopted by the Land Office in 2000. This system is basically a registration system of land titles through the use of computer. CLRS does provides various advantages in terms of reducing time used in the registration process, improved storage system, and enhanced effectiveness as it only focused on process of registration. Furthermore, as the system adopts the Local Area Network (LAN), it provides a better security as it is not open to public at large. However, despite the advantages offered, there are still loopholes that could defeat the effectiveness of CLRS. The system does not provide protection for data and compensation to those having interest in the land in cases of illegal transaction. Therefore, there is a need to mitigate the defects so that the system could serve its main purpose which is, providing an effective land administration system.